Development of Climate Requirements for Compatibility of Land Cocoa in Polewali Mandar District - A. Karim, Harli; Asrul, Laode; S., Baja; Padjung, R.; Neswati, R. (Journal of Agriculture and Applied Biology, 2020)
Cocoa as leading plantation commodities which is quite essential for the national economy that decreasing productivity from 2012 to 2018. The low productivity of cocoa is caused by the fact that cocoa plants that are planted do not meet the optimum growth requirements. Land quality as an optimal growth factor varies greatly in land and time quality, so it requires an in-depth study, one of which is the parametric approach. This approach ana-lyzes the land requirements climate for the suitability of specific cocoa plan-tations in particular regions, so this study aims to determine the characte-ristics of the land that correlate with cocoa productivity in a specific region. The study was conducted from July to December 2019. Also, this study aims to establish a land index through a deductive parametric approach in the Polewali Mandar district as a sample of research locations. The Research purpose of this study was to determine the land characteristics climate) in Polewali Mandar District. This study used a qualitative-quantitative mix analysis. Quantitative analysis is used in determining the correlation be-tween land characteristics climate and cacao production in each sub-district. Determination of land characteristics climate that has a significant effect using regression analysis Primary data were obtained from direct observation, while secondary data were obtained from related institutions. Besides, the determination of the profile location based on production data and cocoa crop distribution through satellite imagery. Qualitative and quan-titative analysis using regression data analysis was used. The results showed that the climate and soil conditions of the Polewali Mandar District were very suitable for the level of land suitability. All parameters tested in this study illustrate that land characteristics climate in the Polewali Mandar District is very suitable for the optimum growth requirements of cocoa plants.